Lewis, P. (2016). Quantum Ontology: A Guide to the Metaphysics of Quantum Mechanics. Oxford University Press. 232pp. - García Martínez, Luis Miguel (Universidad Panamericana. Facultad de Filosofía, 2017)
Quantum Ontology: A guide to the Metaphysics of Quantum Mechanics by P. Lewis, is a book with a philosophical orientation devoted to delve into the metaphysics of quantum mechanics. This book provides a comprehensive and detailed study to the various interpretations of quantum mechanics and their metaphysical consequences in relation to indeterminism, locality, free will, probability, holism and many other topics. Due to its rich philosophical perspective the author has dispensed with the mathematical formalism aiming to a rigorous conceptual approach.
Keywords: Reseña; Filosofía de la física; Mecánica cuántica; Filosofía de la ciencia